Calling in the soul : gender and the cycle of life in a Hmong village - Symonds, Patricia V. (Book collections on Project MUSE., 2004)
""Calling in the Soul" (Hu Plig) is the chant the Hmong use to guide the soul of a newborn baby into its body on the third day after birth. Based on extensive original research conducted in the late 1980s in a village in northern Thailand, this ethnographic study examines Hmong cosmological beliefs about the cycle of life as expressed in practices surrounding birth, marriage, and death, and the gender relationships evident in these practices." "The social framework of the Hmong (or Miao, as they are called in China, and Meo, in Thailand), who have lived on the fringes of powerful Southeast Asian states for centuries, is distinctly patrilineal, granting little direct power to women. Yet within the limits of this structure, Hmong women wield considerable influence in the spiritually critical realms of birth and death."--Jacket